Análise multidimensional do preparo de canais radiculares curvos com instrumentos de níquel-titânio em rotação contínua e reciprocante - Mamede Neto, Iussif (2016)
Objective: To evaluate transportation (T) and centering ability (CA) of root canal preparations using continuous or reciprocating nickel-titanium endodontic files. Material and methods: Ninety-six mesiobuccal root canals of mandibular first and second molars were randomly divide into 6 groups (n=16) according to the rotary file used: Group 1- ProTaper Next®; Group 2- ProTaper Gold®; Group 3- Mtwo®; Group 4- BioRaCe®; Group 5- WaveOne Gold®; Group 6- Reciproc®. Root canals were prepared according to manufacturer’s instructions. Cone-beam computed tomography scans were obtained before and after canal preparation. Measurements were made at five different points: 2, 3 and 4 mm from the apex and 2, 3 and 4 mm below furcation. Transportation and centering ability were analyzed following the recommendations made by Gambill et al. (1996). Results: The greatest mesiodistal (MD) transportation (T) was found for Reciproc® files (p<0.05), and the greatest buccolingual (BL) T, for Reciproc®, ProTaper Gold® and ProTaper Next® files (p<0.05). The greatest mesiodistal (MD) centering ability (CA) was found for BioRaCe® files (p<0.05), and the greatest buccolingual (BL) CA, for BioRaCe® and Mtwo® files (p<0.05). Conclusion: All systems produced root canal transportation. No file system achieved perfect CA of root preparation. Reciproc® files had the greatest MD T and BL T. BioRaCe® files had the greatest MD CA, whereas BL CA was similar for BioRaCe® and Mtwo® files.